2017
DOI: 10.1007/s11027-016-9734-8
|View full text |Cite
|
Sign up to set email alerts
|

Local and Indigenous management of climate change risks to archaeological sites

Abstract: Hundreds of thousands of significant archaeological and cultural heritage sites (cultural sites) along the coasts of every continent are threatened by sea level rise, and many will be destroyed. This wealth of artefacts and monuments testifies to human history, cosmology and identity. While cultural sites are especially important to local and Indigenous communities, a stall in coordinated global action means adaptation at a local scale is often unsupported. In response, this paper produces a practical climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
(66 reference statements)
0
48
0
1
Order By: Relevance
“…Some recent studies conducted in Australia, Canada, U.K., and the U.S. found that climate adaptation prioritization is needed to make transparent decisions between what cultural resources to protect and preserve (for both current and future generations) and what cultural resources to release or "let go" e.g., [9,[58][59][60]. As such, prioritization decisions need to be informed by deliberation with multi-level actors about feasible strategies that integrate the significance of cultural resources with climate change vulnerabilities to ensure continued preservation of diverse heritage values and resources [61].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies conducted in Australia, Canada, U.K., and the U.S. found that climate adaptation prioritization is needed to make transparent decisions between what cultural resources to protect and preserve (for both current and future generations) and what cultural resources to release or "let go" e.g., [9,[58][59][60]. As such, prioritization decisions need to be informed by deliberation with multi-level actors about feasible strategies that integrate the significance of cultural resources with climate change vulnerabilities to ensure continued preservation of diverse heritage values and resources [61].…”
Section: Discussionmentioning
confidence: 99%
“…Pollard-Belsheim et al [20] investigated the effectiveness of existing adaptation strategies to preserve coastal archaeological sites with a focus on a range of adaptation solutions such as watertight barriers, wooden breakwaters, and gabion rock wall. Climate change adaptation solutions to archaeological sites were also studied by Carmichael et al [21] in indigenous communities in Australia. In the Republic of Tartasan in Russia, Usmanov et al [33] suggested adaptation measures to preserve coastal archaeological sites from coastal erosion such as building breakwaters, changes in land use and planting trees.…”
Section: Adapting Cultural Heritage To Climate Change Risksmentioning
confidence: 99%
“…Efforts in the area of adaptation are yet limited to the dissemination of guidelines and recommendations for implementing adaptation measures [1,[16][17][18][19][20][21][22][23][24][25], the identification of the determinants of adaptive capacity [26], and the identification of the barriers to adaptation [27][28][29][30]. Sabbioni et al [1,16] developed guidelines for adapting the European cultural heritage to climate change impacts, which were later adopted by the Italian Strategic Agenda [31,32].…”
Section: Adapting Cultural Heritage To Climate Change Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Research accomplished to date on adapting our cultural heritage to climate change centres on the dissemination of guidelines and recommendations to implement adaptation measures (Sabbioni et al, 2010, Sabbioni et al, 2008, Heathcote et al, 2017, Haugen and Mattsson, 2011, Cassar, 2016, Pollard-Belsheim et al, 2014, Carmichael et al, 2017a, Fatorić and Seekamp, 2017a, Grøntoft, 2011, Hall, 2015 and on the identification of opportunities and barriers to adaptation (Phillips, 2014, Fatorić and Seekamp, 2017b, Carmichael et al, 2017b, Casey, 2018, Sesana et al, 2018. Preserving cultural heritage from the impacts of climate change requires a shift from reactive to proactive adaptation (Sesana et al, 2018).…”
Section: Cultural Heritage and Climate Changementioning
confidence: 99%